A brief history of galectin evolution - Günther, Juliane; Galuska, Sebastian Peter (Frontiers in Immunology, 2023)
Galectins are a family of carbohydrate-binding proteins found in vertebrates in great abundance and diversity in terms of both structure and ligand-binding properties as well as physiological function. Proteins with clear relationships to vertebrate galectins are already found in primitive Bilateria. The increasing amount of accessible well-annotated bilaterian genomes has allowed us to reveal, through synteny analyses, a new hypothesis about the phylogenetic history of the galectin family in this animal group. Thus, we can trace the genomic localization of the putative ancestral Bilateria galectin back to the scallops as a still very primitive slow-evolving bilaterian lineage. Intriguingly, our analyses show that the primordial galectin of the Deuterostomata most likely exhibited galectin-8-like characteristics. This basal standing galectin is characterized by a tandem-repeat type with two carbohydrate recognition domains as well as by a sialic acid binding property of the N-terminal domain, which is typical for galectin-8. With the help of synteny, the amplification of this potential primordial galectin to the broad galectin cosmos of modern jawed vertebrates can be reconstructed. Therefore, it is possible to distinguish between the paralogs resulting from small-scale duplication and the ohnologs generated by whole-genome duplication. This allows us to reveal new theories on the kinship relationships of the galectins of Gnatostomata. Our studies also highlight a previously neglected member of the galectin family, galectin-related protein 2. This protein appears to be a widespread ohnologue of the original tandem-repeat ancestor within Gnathostomata that has not been the focus of galectin research due to its nonclassical galactose binding sequence motif and the fact that it was lost during mammalian evolution.